PRESTASI ULAMA PADA ERA STAGNASI PEMIKIRAN FIQHI - Rustina N Rustina N (Jurnal Studi Islam, 2022)
This study aims to describe the condition of Islamic law when it arrived at the era and period of Islamic jurisprudence. stagnant, starting in the middle of the 4th century H until the XII century H. and analyzing the factors that caused the taqlid attitude and how the role of the fiqhi scholars in this era. Types of qualitative descriptive research, including library research, namely research in which all data, both primary and secondary data, are obtained from the literature, in the form of books or books related to the research subject. The data analysis was carried out through content analysis techniques, namely the effort to describe and analyze in depth the contents of a written or printed information objectively and systematically to reveal the message contained in it. The results of this study are the causes of taqlid attitudes are the students' strong fanaticism towards teachers, school fanaticism, court institutions that are suppressed based on certain schools of thought, and the publication of fiqhi codification works of priests, moral decadence that occurs widely so that the door to ijtihad is closed. The activities of the ulama as scientific achievements have brought a fragrance and raised their degrees, namely mentakhrij illat-illat law which has been assigned by the priests of the schools so that the basics of thought (ushul fiqh) of their schools become clear, conduct tarjih of various differences of opinion, conduct discussions and debates. which gave birth to writings on the ethics of debating, as well as codifying in the form of al-masanid, al-mustadrak, mukhtasar, hawasy, takmilat, fiqhi, ushul fiqh, and fatawa. Penelitian ini bertujuan mendeskripsikan kondisi hukum Islam ketika sampai pada era dan periode stagnan,  dimulai  pertengahan abad ke-4 H sampai abad XII H. dan menganalisis faktor-faktor penyebab terjadinya sikap taqlid tersebut dan bagaimana peran para ulama fiqhi pada era ini.  Tipe Penelitian deskriptif kualitatif, termasuk penelitian pustaka yakni penelitian yang seluruh datanya, baik data primer maupun data sekunder diperoleh dari literatur kepustakaan, berupa buku-buku atau kitab yang berkaitan dengan subyek penelitian. Adapun analisis data dilakukan melalui teknik analisis isi, yaitu usaha menguraikan dan menganalisis secara mendalam isi suatu informasi tertulis atau tercetak secara obyektif dan sistematis untuk mengungkapkan pesan yang terkandung di dalamnya. Hasil penelitian   ini adalah penyebab sikap taqlid adalah sikap fanatisme yang kuat murid-murid kepada guru, fanatisme mazhab, lembaga pengadilan yang ditekan berpedoman pada mazhab tertentu, dan terbitnya karya kodifikasi fiqhi para imam, dekadensi akhlaq yang terjadi secara luas sehingga pintu ijtihad pun ditutup. Aktifitas ulama sebagai prestasi ilmiah yang telah membawa harum serta mengangkat derajat mereka, yaitu mentakhrij illat-illat hukum yang telah diistimbathkan para imam mazhab sehingga dasar-dasar pemikiran (ushul fiqh) mazhab mereka menjadi jelas, melakukan tarjih berbagai perbedaan pendapat, melakukan diskusi dan debat yang melahirkan karya tulis tentang etika berdebat, serta melakukan kodifikasi dalam bentuk al-masanid, al-mustadrak, mukhtasar, hawasy, takmilat, fiqhi, ushul fiqh, dan fatawaa.